Additional Transmissions of Hundsfeld and Lignitzer Dagger Teachings - Bartłomiej Walczak; Bartosz Starko (Bern Open Publishing, 2018)
Additional witnesses containing fragments of Martin Hundsfeld and Andre Lignitzer's dagger teachings were located. These teachings were part of other anonymous dagger texts. Five of Lignitzer's plays and three Hundsfeld's can be found in the works of Gregor Erhart (MS E.1939.65.354), Lienhart Sollinger (Cgm 3712) and Paulus Hector Mair (C.94, Codex 10825). A synoptic comparison of these witnesses with other representatives points to the existence of at least two other manuscripts - one that was base for Erhart and Sollinger, and the other being the base for Paulus Hector Mair's works. Additionally, the analysis seems to suggest that the Proto-Erhart was based on the original proto-manuscript, not transmitted through other known sources. Interestingly, Erhart seems to be a faithful copy of its progenitor, even though it contains a very disorganized text, where dagger techniques are mixed with other weapons. The article contains transcriptions as well as updated stemmae codicum for these traditions.